If at first you don't succeed: Assessing influences associated with mothers' reoffering of vegetables to preschool age children. (1st April 2018) - Holley, Clare E.; Farrow, Claire; Haycraft, Emma
Abstract: Repeatedly offering vegetables has been shown to be one of the most effective methods for increasing acceptance and subsequent intake in young children. In order to increase successful offerings of vegetables and resultant consumption amongst young children, it is necessary to consider the influences on maternal reoffering of vegetables. This study aimed to investigate the relationships between mothers' tendency to reoffer vegetables and a range of demographic factors and psychological variables. A cross-sectional design was used, where mothers completed questionnaires assessing how often they reoffer rejected vegetables, concerns for economic factors, and a range of possible child and maternal influences. Mothers of preschool children were recruited from toddler groups across Leicestershire, UK, as well as online. Spearman's correlations were run to look for associations between demographic and psychological factors with maternal reoffering of vegetables. Significantly associated factors were then entered into a stepwise regression to predict maternal reoffering of vegetables. Mothers were significantly less likely to reoffer rejected vegetables if they were concerned about time, money, and waste, were influenced by their child's mood, or were concerned about their child having tantrums. Moreover, mothers who consumed more vegetables themselves reoffered vegetables more frequently. Regression analyses revealed that mothers' concern about food waste and tantrums, as well as maternal vegetable consumption, all significantly predicted mothers' reoffering of vegetables. With these findings in mind, mothers should be educated and supported with how to tackle and minimise children's tantrums during feeding, as well as being made aware of effective methods for avoiding food waste. Moreover, given that mothers' own vegetable consumption is associated with lower reoffering of vegetables to their child, interventions which seek to increase familial vegetable consumption should be pursued.